Kinerja Guru Bimbingan dan Konseling dalam Layanan Bimbingan Karir - Ehdatul Puadi Siregar; Afdal Afdal; Rezki Hariko (Departement of Mathematics Education, 2024)
Guidance and Counseling are professional services provided by BK teachers. One of the services in guidance and counseling to help students achieve growth, development, explore and make career decisions rationally and realistically based on information, self-understanding and planning to achieve success in their lives, with career guidance services. The purpose of this writing is to socialize the role of guidance and counseling teachers in implementing the career guidance services guidance and counseling program in schools and provide information about career guidance services activities that can be implemented in schools. Career guidance services are provided so that students get the career information they need so that students can make thorough career plans.